Iatrogenic intestinal perforation in umbilical cord hernia - Şenay Kurtuluş (Elsevier, 2020)
We report a case of 1-day-old boy referred with suspicion of umbilical cord hernia, who had a broad based umbilical cord. Iatrogenic intestinal perforation due to clamping of an umbilical cord hernia which contained intestinal loop was noticed after the clamp unlocked. This complication resulted from failure to diagnose umbilical cord hernia and application of the cord clamp too close to the umbilical ring.